Advancement of plant-based inhibitor acquired from Elaeocarpus aungustifolius Blume leaves to control carbon steel corrosion in simulated concrete pore solution - Gautam, Madhab; Subedi, Dhruba Babu; Paudel, Yuvraj; Magar, Kamal T. Kunwar; Bhattarai, Nootan Prasad; Bhattarai, Jagadeesh (BIBECHANA, 2025)
The extraordinary compressive strength of concrete makes it one of the most popular building materials, second only to water. However, early reinforcement corrosion is a common problem with concrete structures reinforced with carbon steel (CS). This issue underscores the significance of understanding corrosion-retarding systems that incorporate inhibitors. This research evaluates the effectiveness of leaf extract from Elaeocarpus angustifolius Blume (LEEA) as an environmentally friendly corrosion inhibitor in a saturated calcium hydroxide solution that simulates a concrete pore solution (SCPS) with a pH level exceeding 11.5. The objective was to evaluate the corrosion-inhibiting capacity of LEEA at concentrations of 500, 1000, 2000, and 4000 ppm in SCPS to reduce reinforcing carbon steel (RCS) corrosion at a laboratory temperature of 298K over four months or more using gravimetric weight loss (GrWL) and electrochemical polarization (ECP) techniques. GrWL and ECP methods yielded the maximal inhibition efficiencies of 93.9% and 81.7%, respectively, at 4000 ppm LEEA in SCPS. The results of ECP experiments demonstrated that the corrosion current density (CCD) decreased with increasing LEEA concentrations. This observation indicates that LEEA exhibits a significant inhibitory effect in the SCPS environments. Phyto-compounds (PCs), including polyphenols, alkaloids, and flavonoids found in LEEA, can inhibit both cathodic and anodic (i.e., mixed) processes by promoting the best-fitting Langmuir adsorption isotherm model on the RCS surface. Surface analyses, such as white light interferometry (WLI), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX), confirmed the corrosion-inhibiting effectiveness of LEEA in enhancing concrete’s anti-corrosion properties through a passive layer on RCS.